Sociodemographic Predictors Associated with the Willingness to Get Vaccinated against COVID-19 in Peru: A Cross-Sectional Survey - Vizcardo, David (2021)
During the race for the development of a vaccine against COVID-19, even before itscommercialization, part of the population has already shown a growing fear of its application. Wedesigned an analytical cross-sectional study using an anonymous survey in the 25 departmentsof Peru. We surveyed whether the participants were planning on getting vaccinated, as well asother characteristics that were cross-checked in a uni-, bi- and multivariate manner. Of the 1776respondents, 70% (1251) stated that they were planning to be vaccinated, 20% (346) did not knowyet or doubted it, and 10% (179) did not want to be vaccinated. We observed that those who did notget infected with COVID-19 exhibited a higher frequency to not wanting or were uncertain aboutgetting vaccinated (aPR: 1.40; 95% CI: 1.09–1.81;p-value = 0.008). In contrast, there was a lowerfrequency of vaccine refusal among university students (aPR: 0.75; 95% CI: 0.61–0.92;p-value = 0.005)and healthcare workers (aPR: 0.59; 95% CI: 0.44–0.80;p-value = 0.001); adjusted by place of residence.There is still an important percentage of respondents who do not want to be vaccinated or are hesitantto do it, which was associated with educational level, being a healthcare worker and if they werepreviously infected with COVID-19. Our results could offer useful information about COVID-19vaccination campaigns.